Street, landscape and courtyard: study on the essence of public space in Islamic built environment - Darkhani, Faiza; Asif, Nayeem; Utaberta, Nangkula; Sabil, Azmal; Mohd Ali, Mohd Hafiz; Rahman, Zaim Akmal Abd (Science Publishing Corporation, 2019)
This paper explores the elements that shape the public spaces in Islamic cities. A sharp contrast has been highlighted between early era of Islamic cities and contemporary era. The main characteristic of public space are accessibility and usability for all citizens. However, current developments, primary observed in cities, suggest the loss of a clear distinction between public and private space. Space with public functions like mosques, courtyard and bazar are changing in character are spreading. This study focuses on three major components such as street market, landscape and courtyards. Further study in this regard are suggested to explore the characteristics of public spaces in Islamic cities in depth in order to compare among regions, cultures and different time periods